2011
DOI: 10.1007/s00784-011-0629-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Emdogain® and platelet-derived growth factor on the osteoinductive potential of hydroxyapatite tricalcium phosphate

Abstract: The aim of this study was to determine whether hydroxyapatite β-tricalcium phosphate (HA-TCP) either alone or coated with Emdogain (EMD) or recombinant human platelet-derived growth factor-BB (rhPDGF-BB) becomes osteoinductive in the murine thigh muscle model for osteoinduction. Twenty CD1 adult male mice had gelatin capsules implanted into the thigh muscle of both hind limbs. The capsules were either empty or contained one of the following: uncoated particulate HA-TCP, EMD-coated HA-TCP or rhPDGF-BB-coated HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Osteogenic processes around granules observed in this study resembled membraneous osteogenesis with the stages osteoid formation, mineralization, generation of fibrous bone, and later remodeling into mature bone, which demonstrates the osteoconductive property of bone substitute materials as already described in previous studies [13,16,23]. Findings from animal experiments could not evidence any osteoinduction upon BCP application, as ectopic bone formation could not be observed [17,18]. However, our results are in concordance with studies analyzing undecalcified specimens that certify intimate contact between newly formed bone and BCP surfaces, which provides tissue stability and volume preservation as important factors for clinical success of augmentation and implant long-term stability [6,15,19].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Osteogenic processes around granules observed in this study resembled membraneous osteogenesis with the stages osteoid formation, mineralization, generation of fibrous bone, and later remodeling into mature bone, which demonstrates the osteoconductive property of bone substitute materials as already described in previous studies [13,16,23]. Findings from animal experiments could not evidence any osteoinduction upon BCP application, as ectopic bone formation could not be observed [17,18]. However, our results are in concordance with studies analyzing undecalcified specimens that certify intimate contact between newly formed bone and BCP surfaces, which provides tissue stability and volume preservation as important factors for clinical success of augmentation and implant long-term stability [6,15,19].…”
Section: Discussionsupporting
confidence: 66%
“…In a study evaluating the healing of the same BCP as used in this study after sinus lift, Frenken et al [16] have also investigated decalcified biopsy specimens, however, using standard histological staining. Immunohistochemical analyses were successfully applied in some animal studies investigating the behavior of ectopic BCP combined with enamel matrix derivative or platelet-derived growth factor in mice [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in immunocompromised mice have revealed that PDGF (Ranly et al, 2005) and platelet-rich plasma (Ranly et al, 2007) decrease the osteoinductivity of DBM. Furthermore, a recent study comparing the osteoinductive effects of a hydroxyapatite/TCP scaffold in combination with enamel matrix derivative or PDGF displayed no signs of osteoinduction in a murine thigh muscle model in mice (Chan et al, 2011).…”
Section: Osteoinductive Principle 3: Ectopic Bone Formationmentioning
confidence: 98%
“…In an ectopic transplantation model, EMD consistently did not exhibit an osteoinductive effect. 22,24,39,40 When space was provided by defect preparation or the use of a membrane, the outcomes were heterogeneous. 17,20,25 EMD application in a membrane-protected space did not influence bone regeneration in rats, 25 whereas EMD in combination with BCP or bovine bone mineral induced significant new bone formation in cylindrical defects in dog mandibles and rat femurs.…”
Section: Discussionmentioning
confidence: 99%